Manifestaciones orales en pacientes con covid-19: revisión bibliográfica - Sánchez Vire, Andrea Priscila (2022)
On March 11, 2020, the Director General of the WHO declared the COVID 19 pandémica; due to the rapid expansion of new cases of pneumonia caused by a new coronavirus; which generally causes: high fever, cough, fatigue, headache, diarrhea, dyspnea; and, at the level of the oral cavity, different clinical manifestations can be found, in view of the presence of the ACE2 and TMPRSS2 enzymes that interact with the virus. That is why, in the present investigation, the oral clinical manifestations produced by the virus (SARS-CoV-2) in patients with COVID-19 were analyzed; through a bibliographic review taking into account the inclusion and exclusion criteria. Obtaining the following results, the most frequent oral manifestations are: taste alterations (ageusia, dysgeusia and hypogeusia) 89.5%, oral ulcers 63.2%, xerostomia 42.1% and 31.6% oral blisters and enanthems (macules and papules). The most affected areas of the oral cavity are the tongue 94.44%, oral mucosa 83.33%, palate 50.00% and lips 38.89%. In view of presenting taste alterations in 90.00%, they are considered as pathognomonic manifestations. In conclusion, the most frequent oral manifestations that can be considered pathognomonic signs are taste disturbances. And when there are other signs and symptoms, the most affected area is the tongue